PEDAGOGICAL CONDITIONS OF FORMATION OF MUSICAL INTERESTS OF JUNIOR SCHOOLCHILDREN IN MUSIC LESSONS - L.I. Kosyak (Academy of Cognitive and Natural Sciences, 2010)
The article deals with the pedagogical conditions that contribute to the successful formation of musical interests of junior schoolchildren in music lessons.